A comparative analysis of the quality of 2007 and 2011 general elections in Nigeria : an evaluation of the independent of National Electoral Commission - Oladele, Adejumo Abdulhakeem (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study of the 2007 and 2011 elections examines the legal and institutional status of the INEC, and the role it played in the management of the two elections. It aims, in particular, to analyse the difference in the INEC's management of the two elections, the volume of structure of personnel and machinery it has established to ensure good management of the elections, the volume of autonomy it wielded during the elections and the quality of their eventual outcome. This study argues that election quality is dependent on the level of autonomy and capacity of the Election Commission. The study determines the variations in the quality of the 2007 and 2011 elections, the degree of capacity of autonomy possessed by the INEC and its effect on the management of the two elections. Semi-structured interviews were conducted to obtain the perspectives of INEC officials and political party executives on the level of autonomy and capacity possessed by the INEC. Various legal instruments were analysed to explain the INEC's power under the law and the control it can exercise over the electoral process. Also, the reports of local and foreign election observers were discussed to understand the volume of autonomy and capacity exercised by INEC during the two elections. An expert panel of university lecturers was selected and they were administered questionnaires to assess the quality of INEC's implementation of each stage of the 2007 and 2011 electoral process. The study found important variations in the conduct and outcome of the two elections. The legal framework of the 2011 elections confers more institutional, operational and financial autonomy on INEC and this invariably, better enhanced the capacity of the INEC during the 2011 elections. Also, it is discovered that the recommendations of the 2010 electoral reform that were injected into the legal framework of the 2011 elections set the stage for major departure from the provisions of the 2007 elections. The legal framework of the 2011 elections confered more financial and administrative autonomy on the INEC and invariably, greater financial autonomy implies a more enhanced capacity in the management of elections. The findings are in agreement with the hypothesized relationship that an institutionally independent election management body is positively related to quality elections and that greater capacity of the electoral management body enhances the quality of elections. The results provide strong evidence that the INEC that managed the 2011 elections was more autonomous and capable than the one that managed the 2007 elections. The results further demonstrated that the quality of the 2011 elections that was managed by the more autonomous and more capable INEC was better than that of the 2007 election.